Response of Porous Seabed to Nature Loadings: Waves and Currents - Ye, J. H; Jeng, D.-S (Journal of engineering mechanics, 2012)
AbstractIn real ocean environments, currents generally exist simultaneously with ocean waves. However, the most previous investigations for the seabed response have only considered wave loading, ignoring currents. In this study, unlike previous studies, currents are included in the model of seabed response with waves, based on Biot’s poroelastic dynamic theory (u-p approximation). Numerical results reveal that the consideration of currents has significant effect on the seabed response. The opposing current is beneficial to prevent liquefaction, while the following current would worsen the stability of the seabed. The parametric studies indicate that the wave period, water depth, saturation, soil permeability, and thickness of the seabed significantly affect the seabed response under combined loading of waves and currents. The maximum relative difference of the pore pressure between the cases with currents (velocity is -2  m/s) and without currents (pcurrent-pnocurrent)/p0 can reach up to 25% in both coarse and fine sand. The analysis of transient liquefaction in the fine sand seabed indicates that the maximum liquefaction depth increases with the following currents, but it decreases with the opposing current.